Bioinformatic identification of key genes and pathways that may be involved in the pathogenesis of HBV-associated acute liver failure - Yalan Yang; Zhaohui Zhong; Yubin Ding; Wanfeng Zhang; Yang Ma; Li Zhou (Genes and Diseases, 2018)
In order to explore the molecular mechanisms behind the pathogenesis of acute liver failure (ALF) associated with hepatitis B virus (HBV) infection, the present study aimed to identify potential key genes and pathways involved using samples from patients with HBV-associated ALF. The GSE38941 array dataset was downloaded from the Gene Expression Omnibus database, and differentially expressed genes (DEGs) between 10 liver samples from 10 healthy donors and 17 liver specimens from 4 patients with HBV-associated ALF were analyzed using the Linear Models for Microarray Data package. Gene Ontology and KEGG pathway enrichment analyses of the DEGs were performed, followed by functional annotation of the genes and construction of a protein–protein interaction (PPI) network. Subnetwork modules were subsequently identified and analyzed. In total, 3142 DEGs were identified, of which 1755 were upregulated and 1387 were downregulated. The extracellular exosome, immune response, and inflammatory response pathways may potentially be used as biomarkers of ALF pathogenesis. In total, 17 genes (including CCR5, CXCR4, ALB, C3, VGEFA, and IGF1) were identified as hub genes in the PPI network and may therefore be potential marker genes for HBV-associated ALF. Keywords: Differentially expressed genes, Function enrichment analysis, HBV-associated ALF, Module analysis, Protein–protein interaction network